In/out: revisiting the relationships between prisons and slums in Latin America - Antillano, Andrés (Punishment in Latin America, 2025)
We propose to see, regarding the Venezuelan context and at the same time in dialogue with the literature on Latin American prisons, the prison through the prison-neighborhood correspondence. This includes, for example, looking at how the prison organizes crime outside, attributes social and reputational capital, extracts and redistributes illegal profits, export/import modes and logics of action and domination. The purpose is to (a) discuss the “hydraulic” theses on prison gangs, dominant in North American literature, which explain their emergence through conditions endogenous of the prison, and instead put the emphasis on the dynamics of exclusion and the “lumpen economies” in which the poor subsist, and (b) nuance the perspectives on the relations between prison and community from the point of view of the peripheral South, marked by high rates of exclusion, informality, and an economy strongly dependent on commodities and a significant labor surplus population, in contrast to the industrial economies of the Global North.